PENGARUH KEPEMIMPINAN DAN KOMUNIKASI KERJA TERHADAP KINERJA ASN (STUDI KASUS DI 4 KECAMATAN) KOTA LUBUKLINGGAU - Yulpa Rabeta (Jurnal Interprof, 2020)
The lack of leader strategy in communicating well to ASN, the lack of leadership attitude in giving attention and motivating ASN work and the lack of work communication among fellow employees resulted in less than optimal ASN performance. This research was conducted to determine the Effect of Leadership and Work Communication on ASN Performance (Case Studies in 4 Sub-Districts) of Lubuklinggau City. Data collection techniques in this study used a questionnaire method. Using SPSS 17.0 Program assistance. Data analysis techniques used are Multiple Linear Regression Analysis, Determination Coefficient (R2), and Test F. From the results of the Multiple Regression Analysis obtained the equation Ŷ = 0.448 + 0.617 X1 + 0.379 X2. Furthermore, from the determinant analysis obtained R square value (R2) of 0.867 or 86.7%. This value gives the meaning that Leadership (X1) and Work Communication (X2) contributed an influence of 86.7% on ASN (Y) Performance. While the remaining 13.3% is influenced by other variables not included in this study. Based on the Anova calculation (F test), it is seen that the Fcount value is 169,645 with a significant level of 0,000 while Ftable with α = 5% and (nk-1) or (55-2-1) = 52. And the numerator (k-2 ) is 3,175. Fcount (169,645) > Ftable (3,175), meaning Ho is rejected and Ha is accepted. This shows that there is a significant influence between Leadership and Work Communication on ASN Performance.